Faktor-Faktor Yang Memengaruhi Motivasi Kerja Pada Lansia - KURNIA SARI, EKA, Wisnu Sri Hertinjung, S.Psi., M.Psi (2017)
Elderly is an end of aging process phase, but along with all population lansia who life in Indonesia, that be unaccompanied with social life level step-up economic, that cause elderly with all physical and also psikis condition decrease, shall work to suffice the need of their life. Besides welfare problem, actually there are many factor which becomes elderly's reason to go on working, one of it because all the kinship faded, that situation makes elderly living in solitude life and less attention. So elderly choose working or looks for activity, despite their financial life actually have been accomplished. To the effect this research is subject to be know and understanding, whatever factors that motivates job on lansia and figuring how that factor memengaruhi motivates lansia to working regulars. Subjects are research are elderly among ages 60-74 years, those are on territorial regency Boyolalis. Acquired data from observation and interview will be analysis. The result of observationaling to point out that elderly at Boyolali regency region still works since to be regarded by two factors, which are internal and external factor. Internal factor covering, physical condition stills healthy and strong, live far away from child, no activity, to meet the need subject, choose working than relies help from child or even others, still wants to interlace social relation with co-worker, and perceiving pleasantly while trip job. External factor, Have fourties years doing a job and talks shop, cozy with work places condition, having good relation with the other co-worker, acquired production can be utilized to suffice requirement.